Deformações estruturais dependentes da energia de Fermi em nanotubos de parede simples - Vieira, Bruno Gondim de Melo (2014)
The carbon nanotubes belong to a group of nanometric materials that are of great interest both for the academic community and for the companies in the technology sector. Due to its unique structure, the carbon nanotubes are among the strongest and hardest materials ever discovered. Furthermore, one of its most interesting features is that many of their mechanical properties are related to their electronic properties, which, in turn, are closely linked to the structural characteristics of the material. For these reasons, these materials have been considered promising for applications as nanoactuators. Therefore, in this work, we investigate the electromechanical actuation of the single-wall carbon nanotubes (SWNTs) through the extended Tight-Binding method (ETB), following the procedure of Verçosa et al. [1]. The energy of the nanotubes is calculated assuming the electron population to follow the Fermi-Dirac distribution for a given Fermi-Energy, which is the parameter we used to simulate this electromechanical actuation. It was verified that the relaxation of the electronic stress generated by the nanotubes Fermi-Energy variation causes high alterations for both the torsional strain and the axial and radial strains for all types of chiral SWNTs, specially for the semiconduting ones. These induced strains directly affects the electronic band structure of the nanotubes, in such a way that great variations in the optical transition energies were observed. Furthermore, it was shown that all these three kinds of strain are of equal importance to the relaxation process, so that all of them are equally responsible for the changes in the optical transition energies. As a result, torsional strains of up to 1% were obtained for the (8,7) nanotube when its Fermi energy is about 1 eV, causing changes of 0,4 eV, approximately, to its optical transition energies.